CTNI-51. ADJUVANT TROTABRESIB, A REVERSIBLE POTENT BROMODOMAIN AND EXTRATERMINAL INHIBITOR, PLUS TEMOZOLOMIDE IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA: INTERIM RESULTS FROM A PHASE 1B DOSE-FINDING STUDY. (12th November 2021) - Vieito, Maria; Simonelli, Matteo; de Vos, Filip; Moreno, Victor; Geurts, Marjolein; Lorenzi, Elena; Macchini, Marina; van den Bent, Martin; Del Conte, Gianluca; de Jonge, Maja; Amoroso, Barbara; Sanchez-Perez, Tania; et al.
Abstract: Trotabresib (CC-90010) demonstrated antitumor activity as monotherapy in patients with advanced malignancies (Moreno et al. ESMO 2020. Abstract 5270) and enhanced the antiproliferative effects of temozolomide in preclinical studies. CC-90010-GBM-002 (NCT04324840) is a phase 1B dose-finding study investigating standard-of-care temozolomide + radiotherapy followed by adjuvant trotabresib + temozolomide or concomitant trotabresib + temozolomide + radiotherapy followed by adjuvant trotabresib + temozolomide, post-resection, in patients with newly diagnosed glioblastoma. We present interim results for adjuvant trotabresib + temozolomide. Patients received trotabresib 15, 30, or 45 mg daily (4 days on/24 days off) + temozolomide administered per label for 6 cycles, followed by trotabresib 45 mg monotherapy daily (4 days on/24 days off). Primary objectives are to establish the safety, maximum tolerated dose (MTD), and recommended phase 2 dose (RP2D) of trotabresib. Preliminary efficacy, pharmacokinetics, and pharmacodynamics are also being investigated. Of 13 patients enrolled, 5, 6, and 2 received trotabresib 15, 30, and 45 mg, respectively, plus temozolomide. Grade 3/4 treatment-related adverse events were reported in 2, 4, and 1 patients receiving trotabresib 15, 30, and 45 mg, respectively. MTD and RP2D are not yet reached; dose limiting toxicity (grade 4 thrombocytopenia) was reported in 1 patient in the 30-mg group. Of 10 evaluable patients, 1 had complete response and 7 had stable disease per RANO criteria. Trotabresib exposure increased proportionally with dose. Day 4 time to peak trotabresib concentration was 0.5–2.0 hours; mean terminal half life was 60–70 hours. Day 4 blood CCR1 RNA 2–4 hours post-dose was downregulated below baseline in the 15-mg group and ≥ 50% in the 30-mg group. Adjuvant trotabresib + temozolomide appears well tolerated, with promising preliminary efficacy. Treatment was ongoing at data cutoff in 9 patients in the adjuvant cohort; enrollment is continuing in the adjuvant and concomitant therapy dose-escalation cohorts.